Analysis of influence of factors on income tax in Ukraine - Shkulipa, Ljudmyla (Technology audit and production reserves, 2018)
The object of research is the factors that can directly or indirectly affect the income tax both at the local and macro level. In the study of the dynamics of changes in the income tax in Ukraine, under the influence of various factors, an abstract-logical method is used, which investigated the significant place of the income tax in the national economy of the country. It is obtained that the tax on the profits of enterprises in Ukraine can be characterized as an analogue of the corporate profits tax in the world. This is due to the fact that large taxpayers, of which less than 1 % of legal entities in Ukraine as a whole, are of great fiscal importance, in particular, provide about 55–59 % of income tax revenue in the consolidated budget. Compared with the EU countries from 2011 to 2016, the income tax rate in Ukraine decreased from 25 % to 18 %, although the country's income has not decreased. The share of income tax in GDP, according to statistics, has tended to decline and is approaching the average level in the countries of the Organization for Economic Cooperation and Development. Factors influencing the income tax and current reforms are considered: the size of the tax rate, GDP, expenditures on scientific and technical work, the volume of financial results of production institutions and organizations before taxation, their seasonal characteristics. Profit tax dynamics significantly influenced the economy of the country, its income and cash flows as a result of all tax changes. The system of taxation of profits of enterprises requires further reform to establish the optimal rate of recovery from profits, eliminate unreasonable benefits, integrate the dividend taxation system, and improve administration. Thus, in 2015–2016, the number of reasons for receiving tax benefits decreased by 4 times – to 24 and 22, respectively.